Inclusion and diversity, heterosexuality, and sex/gender disobedience: theoretical-political-epistemological contributions to rethink CSE pedagogical discourse (Itinerarios Educativos, 2019)
Inclusion and sexual diversity constitute arelevant conceptual binomial in the pedagogical discourseof Comprehensive Sexuality Education (CSE). Giventhe uncritical use of this duo, the purpose of this paperis to reveal some of its political-epistemological implicationsthrough which privileges and subalternities areperpetuated. In this regard, a reflexive analysis basedon the concept of heterosexuality as a political regime ofoppression should be posed with the aim of suggestingthe replacement of a pedagogy based on sexual diversityinclusion by a de-heterosexualizing and celebratorypedagogy based on sex/gender disobedience.
Keywords: inclusion · sexual diversity · cse · heterosexuality · sex/gender disobedience